2017
DOI: 10.1177/1010428317701652
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-34 dysregulation in gastric cancer and gastric cancer stem cell

Abstract: Gastric cancer is a major cause of cancer mortality worldwide, with a low survival rate for patients with advanced forms of the disease. Over the recent decades, the investigation of the pathophysiological mechanisms of tumourigenesis has opened promising avenues to understand some of the complexities of cancer treatment. However, tumour regeneration and metastasis impose great difficulty for gastric cancer cure. In recent years, cancer stem cells -a small subset of tumour cells in many cancers -have become a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 158 publications
(285 reference statements)
0
32
0
Order By: Relevance
“…CSCs are known as a factor for the tumor initiation, progression, metastasis, therapeutic resistance, and recurrence of cancer as well as gastric cancer even years after treatment (Jafari and Abediankenari, ; Zhan et al, ). It is suggested to target both CSCs and none‐CSCs to perform effective cancer therapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CSCs are known as a factor for the tumor initiation, progression, metastasis, therapeutic resistance, and recurrence of cancer as well as gastric cancer even years after treatment (Jafari and Abediankenari, ; Zhan et al, ). It is suggested to target both CSCs and none‐CSCs to perform effective cancer therapy.…”
Section: Discussionmentioning
confidence: 99%
“…It is suggested to target both CSCs and none‐CSCs to perform effective cancer therapy. As a result further understanding and information (stemness markers/futures and signaling pathways) about these cells will help us to achieve this important subject (Jafari and Abediankenari, ; Zhan et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…miRNA has powerful post-transcriptional regulation function and a wide application prospect in tumor therapy. It is reported that many miRNA molecules are expressed abnormally in gastric cancer cells and play important roles in the occurrence and development of gastric cancer (24).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the levels of some miRNAs are abnormal in different types of cancer (33). For example, miR-34 accelerates gastric cancer progression by maintaining cancer stemness properties (34).…”
Section: Microrna-137 Exerts Protective Effects On Hypoxia-induced Cementioning
confidence: 99%